2007
DOI: 10.2522/ptj.20060297
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Extension-Oriented Treatment Approach in a Subgroup of Subjects With Low Back Pain: A Randomized Clinical Trial

Abstract: An EOTA was more effective than trunk strengthening exercise in a subgroup of subjects hypothesized to benefit from this treatment approach. Additional research is needed to explore whether an EOTA may benefit other subgroups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
96
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 38 publications
5
96
2
Order By: Relevance
“…On accordance with these study results Murtezani et al (2015) reported that McKenzie intervention indicates significant change in spinal movement, functional capacity and pain relief among patients with chronic LBP [31]. Likewise, McKenzie's method was more effective than lumbar strengthening exercises in treating non-specific low back pain patients [32]. The author of this study did not find differences between both programs.…”
Section: Discussionsupporting
confidence: 77%
“…On accordance with these study results Murtezani et al (2015) reported that McKenzie intervention indicates significant change in spinal movement, functional capacity and pain relief among patients with chronic LBP [31]. Likewise, McKenzie's method was more effective than lumbar strengthening exercises in treating non-specific low back pain patients [32]. The author of this study did not find differences between both programs.…”
Section: Discussionsupporting
confidence: 77%
“…Data support use of treatment-based classification systems to enhance patient outcomes, 1,2,10,43 but clinical classification data have not been adequately represented in prior risk-adjusted models used to explain FS outcomes. 8,52,54 Data from our research group suggest that the predictive ability of models improves when variables for classifying patients in clinically logical ways are included.…”
Section: Discussionmentioning
confidence: 99%
“…The primary findings of the study suggest that (1) 11 In addition to reliability and validity, the generalizability of a classification system to guide treatment decision making must also be supported. 48 For a classification system to be clinically useful, the system must enhance patient outcomes as well as account for or include a substantial proportion of potential patients referred to rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…5,10 Although the validity for classifying patients into one of the three MDT mechanical subgroups has not been determined, numerous research studies support CEN as an important prognostic factor and classification category for identifying patients who respond favorably from specific CEN-based interventions. [10][11][12][13][14][15][16][17][18][19][20] Classification by patient response criteria including CEN and directional preference for directing treatment have been frequently recommended by clinicians and researchers. 11,[13][14][15][21][22][23][24][25][26][27][28][29] Similar to the three McKenzie syndromes, a substantial proportion of patients (estimates range between 31 and 87%) seen in physical therapy clinics for treatment of low back pain can be classified into a CEN category at intake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation